My precious! The location and diffusion of scientific research: evidence from the Synchrotron Diamond Light Source - Henry Overman; Christian Helmers (European Regional Science Association (ERSA), 2013)
We analyze the impact of the establishment of a GBP 380 million basic scientific research facility in the UK on the geographical distribution of related research. We investigate whether the siting of the Diamond Light Source, a 3rd generation synchrotron light source, in Oxfordshire induced a clustering of related research in its geographic proximity. To account for the potentially endogenous location choice of the synchrotron, we exploit the availability of a 'runner-up' site near Manchester. We use both academic publications and patent data to trace the geographical distribution of related knowledge and innovation. Our results suggest that the siting of the synchrotron in Oxfordshire created a highly localized cluster of related scientific research.
Keywords: 330; Synchrotron; location; innovation; patents